Understanding socioeconomic disparities in travel behavior during the COVID‐19 pandemic. (22nd March 2021) - Brough, Rebecca; Freedman, Matthew; Phillips, David C.
Abstract: We document the magnitudes of and mechanisms behind socioeconomic differences in travel behavior during the COVID‐19 pandemic. We focus on King County, Washington, one of the first places in North America where COVID‐19 was detected. We leverage novel and rich administrative and survey data on travel volumes, modes, and preferences for different demographic groups. Large average declines in travel and public transit use due to the pandemic and related policy responses mask substantial heterogeneity across socioeconomic groups. Travel declined considerably less among less‐educated and lower‐income individuals, even after accounting for mode substitution and variation across neighborhoods in the impacts of public transit service reductions. As policy became less restrictive and travel increased, the size of the socioeconomic gap in travel behavior remained stable, and remote work capabilities became increasingly important in explaining this gap. Our results imply that disparities in travel behavior across socioeconomic groups may become an enduring feature of the urban landscape.